Mono(2-ethylhexyl) phthalate (MEHP) induces transcriptomic alterations in oocytes and their derived blastocysts. (1st June 2019) - Kalo, D.; Vitorino Carvalho, A.; Archilla, C.; Duranthon, V.; Moroldo, M.; Levin, Y.; Kupervaser, M.; Smith, Y.; Roth, Z.
Abstract: Mono(2-ethylhexyl) phthalate (MEHP), the main di(2-ethylhexyl) phthalate (DEHP) metabolite, is a known reproductive toxicant. Residual levels of 20 nM MEHP have been found in follicular fluid aspirated from IVF-treated women and DEHP-treated animals. The current study examined whether these residual MEHP levels have any effect on the follicle-enclosed oocyte or developing embryo. Bovine oocytes were matured with or without 20 nM MEHP for 22 h. Microarray analysis was performed for both mature oocytes and 7-day blastocysts. A proteomic analysis was performed on mature oocytes (n = 200/group) to reveal a possible direct effect on the oocyte proteomic profile. Transcriptome analysis revealed MEHP-induced alterations in the expression of 456 and 290 genes in oocytes and blastocysts, respectively. The differentially expressed genes are known to be involved in various biological pathways, such as transcription process, cytoskeleton regulation and metabolic pathway. Among these, the expression of 9 genes was impaired in both oocytes exposed to MEHP (i.e., direct effect) and blastocysts developed from those oocytes (i.e., carryover effect). In addition, 191 proteins were found to be affected by MEHP in mature oocytes (Data are available via ProteomeXchange with identifier PXD012092). The study explores, for the first time, the risk associated with exposing oocytes to low concentration (i.e., environmentally relevant concentration) of MEHP to the maternal transcripts. Although it was the oocytes that were exposed to MEHP, alterations carried over to the blastocyst stage, following embryonic genome activation, implying that these embryos are of low quality.